A process reference model and a process assessment model to foster R&D&I management in organizations: MGPDI - Weber, K.C.; Machado, C.F.; Machado, R.F.; Magalhães, A.L.; Duarte, A.M.D.; Villalobos, M.T.V.; Schwening, C.; Melchionna, R.; Antonioni, J.A. (Springer Verlag, 2017)
A strategy to foster innovation in organizations consists of the adoption of a Research, Development and Innovation (R&D&I) management model. This paper describes the MGPDI model focused on Process Improvement & Assessment that is applicable to any organization independently of size, type and activity. This new model is based on: (i) requirements based on innovation best practices and Brazilian and Spanish Standards; (ii) the ISO/IEC 330xx family of standards for Process Assessment; (iii) lessons learned with the Brazilian model (MPS) for software process improvement. The MGPDI model has three components: a Process Reference Model (MR-MGPDI), a Process Assessment Model (MA-MGPDI), and a Business Model (MN-MGPDI). This paper also describes the validation of this model and its pilot implementation and assessment in three Brazilian companies. In addition to its relevance in Brazil, it has a high potential for replication in other countries.
Keywords: Process (computing); Process management; Reference model; Relevance (law); Computer science; Business process; Knowledge management; Business; Engineering; Software engineering; Work in process; Operations management; Political science; https://purl.org/pe-repo/ocde/ford#2.02.00